Improvement of hydrogen storage kinetics in ball-milled magnesium doped with antimony. (2nd March 2017) - Cermak, Jiri; Kral, Lubomir; Roupcova, Pavla
Abstract: Kinetics and dynamics of hydrogen storage are studied in magnesium based alloys Mg–Sb–C doped with 5, 13.3 and 21 wt.% of antimony at temperatures between 275 °C and 350 °C. Carbon is added in order to facilitate the ball milling. MgH2 hydride is the principal hydrogen storage phase in all studied alloys. It is found that antimony (i) significantly improves the kinetics of hydrogen sorption compared to hydrogen sorption in pure Mg, and (ii) after long-term ball milling Sb attains the high sorption capacity c max, which approaches the maximum theoretical value of the pure MgH2 hydride, c th = 7.7 wt.% H2 . The high value of c max remains unchanged in the whole temperature interval from 275 °C to 350 °C. At the temperature of 350 °C, the 90% of c max is (ab/de)sorbed typically within approximately 5 min starting with the second sorption cycle. Graphical abstract: Highlights: H2 sorption capacity, c max, approached the high theoretical value of pure Mg. H2 sorption kinetics of Mg–Sb–C was significantly better than that of pure Mg. At 350 °C, 90% of c max was sorbed within approximately 5 min. Principal HS phase in Mg–Sb–C was MgH2 . Sb very slightly destabilized the MgH2 .